A systematic approach to context-mapping to prepare for health interventions: development and validation of the SETTING-tool in four countries - Sally Singh; Bruce Kirenga; Mattijs E Numans; Hilary Pinnock; Maarten J Postma; Niels H Chavannes; Susanne Reventlow; Andy Barton; Grace Ndeezi; Janwillem Kocks; Sian Williams; Winceslaus Katagira; et al. (BMJ Global Health)
Effectiveness of health interventions can be substantially impaired by implementation failure. Context-driven implementation strategies are critical for successful implementation. However, there is no practical, evidence-based guidance on how to map the context in order to design context-driven strategies. Therefore, this practice paper describes the development and validation of a systematic context-mapping tool. The tool was cocreated with local end-users through a multistage approach. As proof of concept, the tool was used to map beliefs and behaviour related to chronic respiratory disease within the FRESH AIR project in Uganda, Kyrgyzstan, Vietnam and Greece. Feasibility and acceptability were evaluated using the modified Conceptual Framework for Implementation Fidelity. Effectiveness was assessed by the degree to which context-driven adjustments were made to implementation strategies of FRESH AIR health interventions. The resulting Setting-Exploration-Treasure-Trail-to-Inform-implementatioN-strateGies (SETTING-tool) consisted of six steps: (1) Coset study priorities with local stakeholders, (2) Combine a qualitative rapid assessment with a quantitative survey (a mixed-method design), (3) Use context-sensitive materials, (4) Collect data involving community researchers, (5) Analyse pragmatically and/or in-depth to ensure timely communication of findings and (6) Continuously disseminate findings to relevant stakeholders. Use of the tool proved highly feasible, acceptable and effective in each setting. To conclude, the SETTING-tool is validated to systematically map local contexts for (lung) health interventions in diverse low-resource settings. It can support policy-makers, non-governmental organisations and health workers in the design of context-driven implementation strategies. This can reduce the risk of implementation failure and the waste of resource potential. Ultimately, this could improve health outcomes.